The protective effect of angiotensin converting enzyme inhibition in experimental renal fibrosis in mice is not mediated by bradykinin B2 receptor activation - Schanstra, Joost P.; Duchene, Johan; Desmond, Laurence; Neau, Eric; Calise, Denis; Estaque, Serge; Girolami, Jean-Pierre; Bascands, Jean-Loup (Thrombosis and Haemostasis, 2003)
Unilateral ureteral obstruction (UUO) is an animal model of accelerated renal tubulointerstitial fibrosis. We have recently shown, using this model, that mice lacking the bradykinin B2-receptor (B2-/-) were more susceptible than control animals to the development of tubulointerstitial fibrosis. Angiotensin converting enzyme (ACE) inhibition slows down UUO-induced renal fibrosis. Since ACE-inhibition increases bradykinin and decreases angiotensin II concentrations we have verified if bradykinin is involved in the antifibrotic effects of ACE-inhibition using the UUO-model and B2-/- mice. Surprisingly, although ACE-inhibition significantly reduced renal fibrosis, no difference was observed between the degree of tubulointerstitial fibrosis, macrophage infiltration and cell proliferation between ACE-inhibitor treated B2+/+ and B2-/- mice suggesting the absence of a role of the B2-receptor in the antifibrotic effects of ACE-inhibition. This was confirmed at the level of bradykinin-induced activity of enzymes involved in the degradation of the extracellular matrix. However in both mouse strains, ACE-inhibitors were more efficient than AT1 receptor antagonists.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: ACE-inhibition; bradykinin; renal fibrosis